Clinical consequences of chemotherapy dose reduction in obese patients with stage III colon cancer: A retrospective analysis from the PETACC 3 study. (August 2018) - Stocker, Gertraud; Hacker, Ulrich T.; Fiteni, Frédéric; John Mahachie, Jestinah; Roth, Arnaud D.; Van Cutsem, Eric; Peeters, Marc; Lordick, Florian; Mauer, Murielle
Abstract: Background: Dose reduction in obese cancer patients has been replaced by fully weight-based dosing recommendations. No data, however, are available on the effects of dose reduction in obese stage III colon cancer patients undergoing adjuvant chemotherapy. Methods: Survival outcomes and toxicity data of obese (body mass index [BMI] ≥30 kg/m 2 ), stage III colon cancer patients treated within the phase III PETACC 3 trial comparing leucovorin, 5-FU (LV5FU2) with LV5FU2 plus irinotecan were analysed retrospectively according to chemotherapy dosing at first infusion (i.e. fully weight-based dosed - versus dose-reduced group). Multivariate analyses on relapse free survival (RFS) and overall survival (OS) were conducted to adjust for baseline prognostic factors using Cox regression model. Results: 13.4% (280 of 2094 patients) had a BMI ≥ 30 kg/m 2, and 5.3% had both a BMI ≥ 30 kg/m 2 and a body surface area (BSA) ≥2 m 2 . Dose reductions occurred in 16.1% of patients with a BMI ≥ 30 kg/m 2 and 32.4% with BMI ≥ 30 kg/m 2 and BSA ≥ 2 m 2, respectively. In patients with BMI ≥ 30 kg/m 2, multivariate analysis demonstrated a trend towards better RFS in the fully dosed compared to the dose-reduced group (Hazard ratio (HR): 0.69, 95% CI: 0.43–1.09; p = 0.11); however, there was no statistically significant difference in OS. In patients with BMI ≥ 30 kg/m 2 and BSA ≥ 2 m 2, multivariate analysis demonstrated better RFS in fully dosed compared with dose-reduced patients (HR: 0.48, 95% CI: 0.27–0.85; p = 0.01) and a strong trend towards better OS (HR: 0.53, 95% CI: 0.28–1.01; p = 0.052). This group comprised predominantly of men. Conclusions: Data support the recommendation of using fully dosed chemotherapy for the adjuvant treatment in obese patients with colon cancer. Highlights: Empiric dose reduction in patients with body mass index ≥30 kg/m 2 and body surface area ≥2 m 2 in the beginning of adjuvant chemotherapy is common practice. Relapse free survival and overall survival is impaired by empiric dose. Men are more affected than women from empiric dose reduction. Fully dosed chemotherapy does not cause more toxicity in men. Data support the recommendation of using fully dosed chemotherapy for the adjuvant treatment of obese patients with colon cancer.